Supply Chain Agility and Internal and External Process Connectivity: The Impact of Supply and Product Complexity - Huynh Xuan Nguyen; Dinh Tran Ngoc Huy; Hong Van Pham (International Journal of Supply Chain Management, 2020)
The study attempts to analyze the impact of internal and external process connectivity on supply chain agility of manufacturing firms in Thailand. It also examines whether supply and product complexity moderates the impact of internal and external process connectivity on supply chain agility. The study relies on the questionnaire survey to collect the data. Using electronic survey, the respondents working in manager’ positions in Thailand’s manufacturing companies are targeted. Out of 250 survey questionnaires, only 173 responses were found usable with a rate of response of 57.2%. The study focuses on Thai firms because Thai manufacturing sector is one of the strongest players in the globe. The reason to select manufacturing firms is that the manufacturing firms are considered to be very crucial in global supply chains in terms of providing agility and responsiveness while delivering final products to the consumers. Supply chain agility (SCAG) is used as dependent while internal process connectivity (INPC) and external process connectivity (EXPC) are used as independent variables. Moreover, product complexity (PRCX) and supply complexity (SPCX) are used as moderating variables. Findings show that SPCX has negatively significant influence on SCAG while PRCX has insignificant effect on SCAG. INPC and EXPC have positive and significant impact on SCAG. The results state that both INPC and EXPC play vital role in attaining SCAG. The interaction effect of product term (INPC × EXPC) on SCAG is also found to be positively significant. These outcomes are in line with the process theory which states that both INPC and EXPC are significant factor that play important role in attaining SCAG. Both these processes permit companies to better respond to continuous variations.